1996
DOI: 10.1007/bf00052509
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the neuroendocrine response in heart failure: Adaptive or maladaptive process?

Abstract: Congestive heart failure is a clinical syndrome in which the capacity of the heart to maintain cardiac output is impaired. As a consequence, blood pressure is threatened and endocrine and paracrine mechanisms are activated to preserve circulatory homeostasis and to maintain blood pressure. At terminal stages, a complex multiorgan syndrome develops with severe pump failure, intense systemic vasoconstriction, and avid water and sodium retention. Increasing evidence points to humoral circulating or locally synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…BNP, is associated with numerous detrimental biological effects that eventually lead to cardiac failure by way of myocyte dysfunction, apoptosis, and cell loss (99). For instance, the ANP gene is expressed in both atrium and ventricle during embryonic development, but its expression is downregulated in the ventricle shortly after birth, leaving the atrium as the primary site of ANP synthesis within the mature myocardium (100).…”
Section: Molecular Basis For Alterations In Myocardial Structure and mentioning
confidence: 99%
See 1 more Smart Citation
“…BNP, is associated with numerous detrimental biological effects that eventually lead to cardiac failure by way of myocyte dysfunction, apoptosis, and cell loss (99). For instance, the ANP gene is expressed in both atrium and ventricle during embryonic development, but its expression is downregulated in the ventricle shortly after birth, leaving the atrium as the primary site of ANP synthesis within the mature myocardium (100).…”
Section: Molecular Basis For Alterations In Myocardial Structure and mentioning
confidence: 99%
“…For instance, the ANP gene is expressed in both atrium and ventricle during embryonic development, but its expression is downregulated in the ventricle shortly after birth, leaving the atrium as the primary site of ANP synthesis within the mature myocardium (100). During myocardial pathologic remodeling, reexpression of ANP in myocytes of the left ventricle takes place (99)(100)(101). Recent studies have demonstrated that ANP is a factor responsible for myocardial apoptosis (49,102).…”
Section: Molecular Basis For Alterations In Myocardial Structure and mentioning
confidence: 99%
“…Neuroendocrine activity occurs via sympathetic and renin angiotensin system, resulting in an increased level of norepinephrine and angiotensin II. Catecholamines and angiotensin II cause a direct increase in the release of von Willebrand factor [48,49,50].…”
Section: Mechanism Of Thromboembolism In Chronic Heart Failurementioning
confidence: 99%
“…14,15 This compensatory mechanism may improve contractility and provide hemodynamic support in short term. However, chronic adrenergic stimulation can be deleterious because it may cause myocardial damage due to changes in left ventricular remodeling, loss of myocardial cells and abnormal gene expression.…”
Section: 7mentioning
confidence: 99%